The Oslo Agreement: A Study of the Conflict Peace Process Arabic-Israel - Fatih Soleimani (GoAcademica Research & Publishing, 2020)
The Oslo Agreement is one of the most important peace processes between Israel and Palestinians aimed at resolving the prevailing conflict. Although this agreement can be seen as an ongoing process, the conflict remains the most troubling issue in the Middle East. This article describes the conflict identification and literature review related to the Declaration of Principles on Interim Self-Government Arrangements (DOP) and the process of formalizing the Oslo Agreement. The conversation between the two parties involved, among others, interpreting rights, boundaries, housing and others. There are different perspectives and views regarding this agreement. Instead, this article analyzes the Oslo Accords including Oslo I and II which were signed in 1993 and 1995 to achieve security in the Middle East.